2012
DOI: 10.1590/s1516-80342012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de erros de fala em crianças com transtorno fonológico em função do histórico de otite média

Abstract: OBJETIVO: Descrever os índices articulatórios quanto aos diferentes tipos de erros e verificar a existência de um tipo de erro preferencial em crianças com transtorno fonológico, em função da presença ou não de histórico de otite média. MÉTODOS: Participaram deste estudo prospectivo e transversal, 21 sujeitos com idade entre 5 anos e 2 meses e 7 anos e 9 meses com diagnóstico de transtorno fonológico. Os sujeitos foram agrupados de acordo com a presença do histórico otite média. O grupo experimental 1 (GE1) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
6
0
4
Order By: Relevance
“…The correlations between the scores on both tests also suggest that these indicators remained an association of values in both tests. The positive correlation observed in G1 between PCC-R and RDI in both tests indicates that the greater the number of correct productions and the distortion, the lower the number of omissions and substitutions (8) . The negative correlation observed in G2 between the PCC-R and the SRI, also confirms that the relation, the higher the PCC-R, the lower the RSI in both tasks.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The correlations between the scores on both tests also suggest that these indicators remained an association of values in both tests. The positive correlation observed in G1 between PCC-R and RDI in both tests indicates that the greater the number of correct productions and the distortion, the lower the number of omissions and substitutions (8) . The negative correlation observed in G2 between the PCC-R and the SRI, also confirms that the relation, the higher the PCC-R, the lower the RSI in both tasks.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study (8) has shown that the absolute and relative indexes identified the most occurrent error type in children with SSD, with cognitive linguistic difficulties, is the substitution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crianças com TF muitas vezes apresentam o conhecimento internalizado da língua prejudicado (Marchetti et al, 2010;Wertzner et al, 2012b). Assim, para alguns autores (Rvachew et al, 2003;Raitano et al, 2004;Rvachew e Grawburg, 2006;Rvachew, 2007) Já em outro estudo, com crianças de 7 a 10 anos de idade com e sem TF, observou-se que as crianças com TF tiveram pior desempenho em todos os subtestes propostos, sugerindo que essas crianças têm dificuldades de consciência fonológica nas habilidades de rima e aliteração (Herrero, 2007).…”
Section: Principais Características Do Transtorno Fonológicounclassified